“I dream of an island”: Black joy, storytelling and the art of refusal. Creative methodologies and decolonial praxis in higher education - Alormele, Naomi (Frontiers in Sociology, 2025)
This paper advances a decolonial and Black feminist intervention into higher education research by positioning emotive storytelling, creative methodologies, and Black joy as transformative tools for epistemic resistance and institutional critique. Centring the voices of Black women in academic and professional roles across the UK and Canada, the study draws on Decolonial Theory, Black Feminist Thought, and Critical Race Theory to examine how contributors navigate systemic exclusion, racialised emotional labour, and the limitations of performative diversity. Using a cross-contextual, contributor-led approach—including storytelling conversations, reflective journals, poetry, and visual artefacts—this research establishes emotive and creative forms of expression as legitimate and vital modes of knowledge production. Black joy is conceptualised not as an affective state, but as a radical methodological and political framework: enacted through humour, ritual, and care, it becomes a strategy of survival, refusal, and reimagining. Storytelling functions as both method and praxis, offering contributors space to articulate lived realities and assert epistemic agency. Visual artefacts—such as collages, metaphorical drawings, and illustrated poetry—are analysed as counter-narratives that disrupt erasure and reframe Black women’s presence within academic institutions. While UK contributors contend with the afterlives of empire and class-based exclusion, Canadian contributors confront the contradictions of multiculturalism and anti-Indigenous racism. Across both contexts, the study exposes how symbolic inclusion masks structural harm. This study contributes to current debates on decolonising research by demonstrating the power of emotionally grounded, arts-based methodologies to surface hidden forms of knowledge and resistance. It calls for institutions to move beyond rhetorical equity by honouring Black women’s intellectual labour, embedding joy as method, and supporting creative, relational approaches to transformation in higher education.